The gender perspective in climate change and global health - Preet, Raman; Nilsson, Maria; Schumann, Barbara; Evengård, Birgitta (Global health action, 2010)
Background: Population health is a primary goal of sustainable development. United Nations international conferences like the Beijing Platform for Action have highlighted the key role of women in ensuring sustainable development. In the context of climate change, women are affected the most while they display knowledge and skills to orient themselves toward climate adaptation activities within their societies. Objective: To investigate how the gender perspective is addressed as an issue in research and policy-making concerning climate change and global health. Methods: A broad literature search was undertaken using the databases Pubmed and Web of Science to explore the terms 'climate change,' 'health,' 'gender,' and 'policy.' Climate change and health-related policy documents of the World Health Organization (WHO) and National Communications and National Adaptation Programs of Action reports submitted to the United Nations Framework Convention on Climate Change of selected countries were studied. Assessment guidelines to review these reports were developed from this study's viewpoint. Results: The database search results showed almost no articles when the four terms were searched together. The WHO documents lacked a gender perspective in their approach and future recommendations on climate policies. The reviewed UN reports were also neutral to gender perspective except one of the studied documents. Conclusion: Despite recognizing the differential effects of climate change on health of women and men as a consequence of complex social contexts and adaptive capacities, the study finds gender to be an underrepresented or non-existing variable both in research and studied policy documents in the field of climate change and health.